Association Between Neutrophil to Lymphocyte Ratio and Severity of Coronary Artery Disease. (January 2014) - Kaya, Hasan; Ertaş, Faruk; İslamoğlu, Yahya; Kaya, Zekeriya; Atılgan, Zuhal Arıtürk; Çil, Habib; Çalışkan, Ahmet; Aydın, Mesut; Oylumlu, Mustafa; Soydinç, Mehmet Serdar
The aim of this study is to investigate the association between neutrophil to lymphocyte ratio (NLR) and severity of coronary atherosclerosis. A total of 172 patients undergoing coronary angiography were included in the study. Control group consisted of patients with normal coronary arteries. Patients with coronary stenosis were divided into 2 groups by use of Gensini scores. The NLR was higher in severe atherosclerosis group compared with mild atherosclerosis and control groups ( P < .001). In correlation analysis, NLR showed significant correlation with Gensini score. A cutoff value of 2.5 for NLR predicted severe atherosclerosis with a sensitivity and specificity of 62% and 69%, respectively. After multivariate analysis, high levels of NLR were independent predictors of severe atherosclerosis together with glucose and high-density lipoprotein. Our study suggests that the NLR is a predictor of severe atherosclerosis that may be useful for cardiac risk stratification in patients with coronary artery disease.